Trinta anos de sintaxe gerativa no Brasil - Kato, Mary A.; Ramos, Jânia (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This paper reports the generativist research developed in Brazil, from the standard theory to the Minimalist approach (Chomsky 1995), leaving out works in language aquisition, which are reported in Kato (1999). It contains three sections: I. The Standard Theory and the Extended Standard Theory; II. The Principles and Parameters Theory; III. The years 1998-1999